Adherence to long-term supportive periodontal therapy in groups with different periodontal risk profiles - Sonnenschein, Sarah K.; Kohnen, Rebecca; Rütters, Maurice; Krisam, Johannes; Kim, Ti-Sun (Journal of clinical periodontology, 2020)
Aim To examine changes of the periodontal risk assessment (PRA) of patients during long-term supportive periodontal therapy (SPT) and to examine the adherence to recommended visit intervals. Material and Methods Retrospective data from 372 SPT patients were evaluated before and after active periodontal therapy (APT) and at least 5 years later. After APT and regularly during SPT, PRA was performed for all included patients (low-risk/moderate-risk/high-risk profile) and they were advised to adhere to 3/6-/or 12-month intervals accordingly. The adherence (fully/partially/insufficiently/non-adherent) to SPT intervals was assessed retrospectively. Results Initially, 38 patients had a low-risk, 217 a moderate-risk and 94 a high-risk profile. Five years after APT, 55.3% of the low-risk, 71.9% of the moderate-risk and 54.3% of the high-risk patients had not changed their initial risk. 19.5% of the moderate-risk group shifted to “high-risk” and 8.6% to “low-risk”. 66% of low-risk, 34% of moderate-risk and 13% of high-risk patients fully adhered to SPT. The portion of non-adherent patients was the highest within the high-risk group (18%-43%). The level of adherence was associated with number of lost teeth and mean PPD (p < .05). Conclusions Risk profiles can change during SPT. A high level of adherence to SPT intervals based on PRA positively influences the periodontal status.